Community-Based Dipstick Urinalysis Screening for Early Detection of Kidney Disorders in Rural Indonesia - Rodhi Hartono; Dina Afrianti (Indonesia Berdaya, 2026)
Chronic kidney disease (CKD) is a major public health problem due to its increasing prevalence, late diagnosis, and limited awareness, particularly in rural communities. Early detection through simple and accessible screening methods is essential to prevent disease progression. This community service program aimed to enhance kidney health awareness and identify early risk factors for renal disorders through the integration of health education and dipstick urinalysis screening among residents of Pundan Village, Banyubiru District, Semarang Regency, Indonesia. The program was implemented using a participatory approach involving 45 adult community members. Activities included interactive health education sessions, urine dipstick screening, basic health measurements, and individualized counseling. The results showed that most participants initially had low knowledge of kidney health, while screening identified several risk indicators related to kidney dysfunction, including metabolic risk factors and abnormal urinalysis findings. The combination of education and hands-on screening improved participants’ understanding of kidney health and encouraged preventive behaviors. This program demonstrates that integrating health education with dipstick urinalysis is a feasible, low-cost, and effective community-based approach for early detection and prevention of kidney disorders. The model can be replicated in other rural settings to support promotive and preventive health efforts and reduce the burden of chronic kidney disease.